Epidemiological profile of obstetric fistula women at the National Obstetric Fistula Reference Center in Niamey; from January 2016 to 31 December 2017 - Idrissa, Abdoulaya; Abdul Rashid, Adamou Moumouni (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe the socio-demographic, clinical and therapeutic aspects of fistula. Methods: It is a retrospective and descriptive study. The sampling method was exhaustive. Results: 140 women with obstetric fistula have been identified. The average age was 27 years old; 87.14% were married; 41% were primiparous; 97.86% were housewives. Urogenital fistula was found in 94% of cases smaller than 2 cm in 56.43%; 51.43% were on their first course; 91% were operated with a cure rate of 32.03% and failure of 16.41%. In 51.56% of cases, the outcome of treatment was not notified. Conclusions: Obstetric fistula remains a public health problem in Niger, given the number of new cases registered. Compared with previous studies, there has been an increase in the average age and an increase in the number of women married with fistula. The completeness of the filling of medical records would allow a better assessment of the quality of care.